Decreased Plasma Hydrogen Sulfide Level Is Associated With the Severity of Depression in Patients With Depressive Disorder - Yang, Yuan-Jian; Chen, Chun-Nuan; Zhan, Jin-Qiong; Liu, Qiao-Sheng; Liu, Yun; Jiang, Shu-Zhen; Wei, Bo (Frontiers in Psychiatry, 2021)
Accumulating evidence has suggested a dysfunction of synaptic plasticity in the pathophysiology of depression. Hydrogen sulfide (H2S), an endogenous gasotransmitter that regulates synaptic plasticity, has been demonstrated to contribute to depressive-like behaviors in rodents. The current study investigated the relationship between plasma H2S levels and the depressive symptoms in patients with depression. Forty-seven depressed patients and 51 healthy individuals were recruited in this study. The 17-item Hamilton Depression Rating Scale (HAMD-17) was used to evaluate depressive symptoms for all subjects and the reversed-phase high-performance liquid chromatography (RP-HPLC) was used to measure plasmaH2S levels. We found that plasma H2S levels were significantly lower in patients with depression relative to healthy individuals (P < 0.001). Compared with healthy controls (1.02 ± 0.34 μmol/L), the plasma H2S level significantly decreased in patients with mild depression (0.84 ± 0.28 μmol/L), with moderate depression (0.62 ± 0.21μmol/L), and with severe depression (0.38 ± 0.18 μmol/L). Correlation analysis revealed that plasma H2S levels were significantly negatively correlated with the HAMD-17 scores in patients (r = −0.484, P = 0.001). Multivariate linear regression analysis showed that plasma H2S was an independent contributor to the HAMD-17 score in patients (B = −0.360, t = −2.550, P = 0.015). Collectively, these results suggest that decreased H2S is involved in the pathophysiology of depression, and plasma H2S might be a potential indicator for depression severity.